Social Support for Postpartum Mothers with Postpartum Depression: Scoping Review - Ikha Muflikha; Rosmita Nuzuliana; Sri Lestari (International Journal of Health Science and Technology, 2021)
Background: In Indonesia, the incidence of postpartum depression accounts for 50% to 70% of postpartum women. Therefore, ladies within the postnatal amount would like a social support from individuals around them to adapts to their new role as mothers. The lower the social support provided, the upper the postnatal depression. Research objective: Collection of articles discussing social support for postpartum mothers with postpartum depression Method: Five stages were wont to conduct scoping a review. The 5 stages embrace characteristic analysis queries, characteristic relevant studies, choosing studies, charting knowledge, and an aggregation, summarizing and reportage the results.Result: It was found that 9 selected literature had Grade A and B. 4 themes emerged as a result of the scoping review comprising of husband support, family support, friend support and self-efficacy for mothers experiencing postpartum depression. The literature was obtained from quantitative and qualitative research originating from developed and developing countries. Conclusion: Social support obtained from husband, family, friends, and self-efficacy is very important to reduce the rate of postpartum depression. The research gap was used as a reference in future research. It is hoped that researchers can develop research on the factors correlated to postpartum depression.